OBC women status and educational empowerment - Singh S K; Singh A K (Lucknow New Royal Book, 2004)
This book highlights the status of OBC woman and discusses the scope of their educational empowerment for over all socio economic development. It also presents critical review of recommendations of various commissions and committees set up by state govern
Keywords: Backward classes; Economic conditions; India; Social conditions; Women